Multi‐level regulation of the chloroplast ATP synthase: the chloroplast NADPH thioredoxin reductase C (NTRC) is required for redox modulation specifically under low irradiance. (6th August 2016) - Carrillo, L. Ruby; Froehlich, John E.; Cruz, Jeffrey A.; Savage, Linda J.; Kramer, David M.
Summary: The chloroplast ATP synthase is known to be regulated by redox modulation of a disulfide bridge on the γ‐subunit through the ferredoxin–thioredoxin regulatory system. We show that a second enzyme, the recently identified chloroplast NADPH thioredoxin reductase C (NTRC), plays a role specifically at low irradiance. Arabidopsis mutants lacking NTRC ( ntrc ) displayed a striking photosynthetic phenotype in which feedback regulation of the light reactions was strongly activated at low light, but returned to wild‐type levels as irradiance was increased. This effect was caused by an altered redox state of the γ‐subunit under low, but not high, light. The low light‐specific decrease in ATP synthase activity in ntrc resulted in a buildup of the thylakoid proton motive force with subsequent activation of non‐photochemical quenching and downregulation of linear electron flow. We conclude that NTRC provides redox modulation at low light using the relatively oxidizing substrate NADPH, whereas the canonical ferredoxin–thioredoxin system can take over at higher light, when reduced ferredoxin can accumulate. Based on these results, we reassess previous models for ATP synthase regulation and propose that NTRC is most likely regulated by light. We also find that ntrc is highly sensitive to rapidly changing light intensities that probably do not involve the chloroplast ATP synthase, implicating this system in multiple photosynthetic processes, particularly under fluctuating environmental conditions. Significance Statement: ATP synthase acts as a key regulator of photosynthesis in response to light and electron flow. Whereas the canonical thioredoxin‐based system of redox regulation of ATP synthase functions at higher light, we show here that NADPH thioredoxin reductase (NTRC) modulates ATP synthase under low and fluctuating light.